Observation of universal dynamics in a spinor Bose gas far from equilibrium - Prüfer, Maximilian; Kunkel, Philipp; Strobel, Helmut; Lannig, Stefan; Linnemann, Daniel; Schmied, Christian-Marcel; Berges, Jürgen; Gasenzer, Thomas; Oberthaler, Markus K. (Nature, 2018)
The emergence of universal dynamics far from equilibrium is observed by evaluating spatially resolved spin correlations in a quasi-one-dimensional spinor Bose-Einstein condensate.